2015
DOI: 10.1515/msp-2015-0075
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Inx(As2Se3)1-x thin films using variable angle spectroscopic ellipsometry (VASE)

Abstract: The results of multi-angle ellipsometrical measurements of thermally evaporated In x (As 2 Se 3 ) 1−x (x = 0, 0.01, 0.05) films are presented. Optical parameters n and E g of thin In x (As 2 Se 3 ) 1−x films show that indium atoms were incorporated into the host matrix of As 2 Se 3 forming distinct features depending on the indium concentration. Refractive index, n, was found to decrease with the addition of In to the binary As 2 Se 3 . The real and imaginary parts of the dielectric function, ε and ε were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thermally evaporated In x (As 2 Se 3 ) 1−x (x = 0, 0.01, 0.05) films were also characterized by VASE. [38] The refractive index and E g were found to decrease while the absorption coefficient increases with In content increasing. The real and imaginary part of the dielectric function, ε 1 and ε 2 were also calculated, and the results showed that ε 1 decreases while ε 2 increases with In content increasing.…”
Section: Němec Et Al (2011)mentioning
confidence: 94%
“…Thermally evaporated In x (As 2 Se 3 ) 1−x (x = 0, 0.01, 0.05) films were also characterized by VASE. [38] The refractive index and E g were found to decrease while the absorption coefficient increases with In content increasing. The real and imaginary part of the dielectric function, ε 1 and ε 2 were also calculated, and the results showed that ε 1 decreases while ε 2 increases with In content increasing.…”
Section: Němec Et Al (2011)mentioning
confidence: 94%